The Efficacy of Psidium guajava Linn Leaf Extractsfrom Selangor Region Against Gram-Positive and Gram-Negative Bacteria - Zuhaira, S; Nizam, Noorhaniz Mohd; Ridzuan, PM (Folia Medica Indonesiana, 2018)
Antibiotic is a type of medication that helps in fighting bacterial infection. Treating bacterial infections in clinical setting become more complicated and costly due to drug resistance. This study was conducted to determine the antibacterial potential of Psidium guajava Linn leaf extracts against Gram-positive and Gram-negative bacteria. P. guajava Linn leaf was obtained from Research Orchards at University Putra Malaysia (UPM). Leaves were extracted using three types of extracts; hot, cold and methanol extract. Freeze dried was used in this study and temperature was set at -104°C for 24 hours. Antibacterial testing was determined using disc diffusion and well diffusion method. Antibacterial activity was evaluated by measuring the inhibitory zone of the tested bacteria. Phytochemical analysis was conducted by adding few drop of diluted NaOH (Sodium Hydroxide) solution to detect the active flavanoid from leaves extract. Antimicrobial activity showed all extracts were effective against Gram-positive and Gram-negative bacteria. Phytochemical analysis of P. guajava Linn leaf extracts showed the methanol extract indicating the presence of tannins, phenols, flavonoids, terpenoids, glycosides and saponins. Results showed that P. guajava Linn leaf was effective against Gram-positive and Gram-negative bacteria, and pythochemical analysis also exhibited a few active compounds that were determined. P. guajava Linn leaf had potential natural product that may be used for further analysis in the future research.